Organocatalytic enantioselective vinylogous michael-aidoi cascade for the synthesis of spirocyclic compounds - Mondal, Santigopal; Mukherjee, Subrata; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
Enantioselective synthesis of pyrazolone-fused spirocyclohexenols by the secondary amine-catalyzed cascade reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones is reported. This formal [3 + 3] organocascade reaction proceeds through a vinylogous Michael-aldol sequence to furnish the spiroheterocycles with three stereocenters including an all-carbon quaternary center in good yields and selectivities. The catalytic generation of alpha,beta-unsaturated iminium ions from enals and tandem dienolate/enolate formation from pyrazolinones are the key for the success of this spiroannulation reaction.